Implications of monetary union for catching-up member states - Marcelo Sánchez (European Central Bank (ECB), 2006)
We examine the implications of monetary union for macroeconomic stabilisation in catching up participating countries. We allow member states'supply conditions to differ inside the union, especially with regard to sectoral characteristics. Sectoral productivity shocks on balance hamper the stabilisation properties of a currency union. In the face of aggregate supply disturbances, the stabilisation costs of renouncing monetary autonomy diminish with a flatter output-inflation tradeoff and - barring idiosyncratic shocks - with a larger reference country size, more homogeneous supply slopes and a higher preference for price stability.
Keywords: E52; E58; F33; F40; 330; Balassa-Samuelson Effect; Exchange Rates; monetary union; price stability; Währungsunion; Wechselkurs; Preisstabilität; Theorie; Balassa-Samuelson-Effekt; EU-Mitgliedschaft